APLIKASI TECHNOLOGY ACCEPTANCE MODEL TERHADAP MINAT MENGGUNAKAN DOMPET DIGITAL DANA - Wijaya, Brenda Jory; Prasetyawati, Yuliana Riana; Mustofa, Muhammad Hasim Habibil (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2023)
Indonesia ranked 2nd (24.3%) among the countries where mobile payment app adoption is growing fastest. One of the newcomers from a startup fintech company, called Dompet Digital Indonesia  (DANA). DANA officially released in 2018 and in less than a year, has reached 20 million users. However, the total active daily users is only 1.5 million, which means the users who are loyal to using DANA are only about 7% of the total users. Therefore, to oversee the market acceptance and effectiveness of DANA as an E-Wallet from the level of user’s attitude and perspective  Technology Acceptance Model (TAM) will be used in this research. The aim of the study is to analyze the effect of perceived usefulness(X1), perceived ease of use (X2), and perceived risk (X3) towards the intention to use E-Wallet DANA. The method used in this research is quantitative with purposive sampling as the sampling technique. The data collection was carried out using an online questionnaire from 100 respondents who are between 19-35 years old and DANA users. The results of this study indicate that partially and simultaneously perceived usefulness (X1) and perceived ease of use (X2) have a positive and significant influence on the intention to use DANA, meanwhile perceived risk (X3) has a negative and significant effect on the intention to use DANA with determination coefficient value of 66.6%. DANA can increase the security factor in order to reduce the level of risk that is perceived by the users.